The Saga of History 492: The Transformation of Working-Class History in One Classroom - Barrett, Jim; Koenker, Diane P. (Labour / Le Travail, 2008)
The article focuses on the educational course History 492 and the relationship between the re-conceptualization and rewriting of working-class history in the U.S. and the ways in which teaching of the subject has changed. The evolution of the course suggests that social class is still being talked about in more capacious terms. It says that the seminar's comparative approach indicates that the characteristics of capitalism and industrialism are shared from one society to another.
Keywords: CURRICULA (Courses of study); Capitalism; HISTORY -- Study & teaching; INDUSTRIALISM; Social classes; United States; WORKING class -- History